2020
DOI: 10.1194/jlr.ra119000551
|View full text |Cite
|
Sign up to set email alerts
|

Schnyder corneal dystrophy-associated UBIAD1 is defective in MK-4 synthesis and resists autophagy-mediated degradation

Abstract: The autosomal dominant disorder Schnyder corneal dystrophy (SCD) is caused by mutations in UbiA prenyltransferase domain-containing protein-1 (UBIAD1), which uses geranylgeranyl pyrophosphate (GGpp) to synthesize the vitamin K2 subtype menaquinone-4 (MK-4). SCD is characterized by opacification of the cornea, owing to aberrant build-up of cholesterol in the tissue. We previously discovered that sterols stimulate association of UBIAD1 with endoplasmic reticulum (ER)-localized HMG CoA reductase, which catalyzes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…4B). The increase in HMGCR protein was much larger than the increase in Hmgcr mRNA, which may be explained by well-documented posttranscriptional regulatory mechanisms of HMGCR (Goldstein & Brown 1990; Jun et al 2020). Mevalonate kinase (MVK, 1.5-fold) and phosphomevalonate kinase (PMVK, 1.9-fold) were also increased in Ehhadh KO livers (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…4B). The increase in HMGCR protein was much larger than the increase in Hmgcr mRNA, which may be explained by well-documented posttranscriptional regulatory mechanisms of HMGCR (Goldstein & Brown 1990; Jun et al 2020). Mevalonate kinase (MVK, 1.5-fold) and phosphomevalonate kinase (PMVK, 1.9-fold) were also increased in Ehhadh KO livers (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…4B). The increase in HMGCR protein was much larger than the increase in Hmgcr mRNA, which may be explained by well-documented posttranscriptional regulatory mechanisms of HMGCR (Goldstein & Brown 1990;Jun et al 2020).…”
Section: Perturbation Of Hepatic Cholesterol Homeostasis In Ehhadh Komentioning
confidence: 90%
“…The pathogenesis of SCCD was then investigated and clarified by consistently exploring the functions of UBIAD1. From research, it was identified that UBIAD1 regulates HMGCR through GGpp in cholesterol biosynthesis and metabolism of significant componential molecules ( 46 , 53 , 54 , 56 , 58 , 59 , 87 , 88 ). UBIAD1 is also a critical tumor suppressor in the urinary system ( 11 , 44 , 47 , 48 , 51 , 88 ) and regulates cell proliferation through the ras signaling pathway ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…A SCCD-related mice model affirms the physiological significance of UBIAD1 in cholesterol homeostasis and demonstrates the inhibition of HMGCR ERAD, contributing to SCCD pathogenesis ( 46 , 58 ). Similarly, Jun et al ( 59 ) establishes a biochemical assay for UBIAD1-mediated synthesis of MK-4 in isolated membranes and intact cells. The results reveal that mutated UBIAD1 exhibited reduced Mk-4 biosynthetic activity compared with wild-type UBIAD1.…”
Section: Subcellular Localization and Functions Of Ubiad1mentioning
confidence: 99%
See 1 more Smart Citation